Evidence from studies in rodents and in isolated adipocytes that agonists of the chemerin receptor CMKLR1 may be beneficial in the treatment of type 2 diabetes - Wargent, Ed T; Zaibi, Mohamed S; O'Dowd, Jacqueline F; Cawthorne, Mike A; Wang, Steven J Y; Arch, Jonathan R S; Stocker, Claire J (PeerJ PrePrints, 2014)
It is unclear whether the adipokine chemerin has pro- or anti-inflammatory properties, plays any role in the aetiology of obesity or type 2 diabetes, or whether agonists or antagonists of the chemerin receptor CMKLR1 have potential in the treatment of these diseases. To address these questions, we investigatedthe metabolic phenotypes of both male and female, CMKLR1 knockout and heterozygote mice; the effects of murine chemerin and some C-terminal peptides on glucose uptake in wild-type and CMKLR1 knockout adipocytes; and plasma chemerin levels and chemerin gene mRNA content in adipose tissue in models ofobesity and diabetes, and in response to fasting or administration of the insulin sensitizing drug rosiglitazone, which also has anti-inflammatory properties. Both male and female, CMKLR1 knockout and heterozygote mice displayed a mild tendency to obesity and impaired glucose homeostasis, but only when they were fed on a high fat, rather than a standard low fat diet. Obesity and impaired glucose homeostasis did not occur concurrently, suggesting that obesity was not the sole cause of impaired glucose homeostasis. Picomolar concentrations of chemerin and its C15- and C19-terminal peptides stimulatedglucose uptake in the presence of insulin by rat and mouse wild-type epididymal adipocytes, but not by murine CMKLR1 knockout adipocytes. The insulin concentration-response curve was shifted to the left in the presence of 40 pM chemerin or its C-15 terminal peptide. The plasma chemerin level was raised in diet-induced obesity and ob/ob but not db/db mice, and reduced by fasting and, in ob/ob mice, by treatment with rosiglitazone. These findings suggest that an agonist of CMKLR1 is more likely than an antagonist to be of value in the treatment of type 2 diabetes and have associated anti-obesity andanti-inflammatory activities. One mechanism by which an agonist of CMKLR1 might improve glucose homeostasis is by increasing insulin-stimulated glucose uptake by adipocytes.
Keywords: Type 2 diabetes; Glucose uptake; Chemerin receptor; Adipocyte; Obesity; Chemerin; Rosiglitazone